(3eONd Gdi Yde GdGbJUGO (B:s (3GdJMdjd GdLRFj h Gdcdj (B/s - (3GdHjGJj, WGgQ aGVds; (3GdTeQj, NGdO Jhajb s ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
1) (3GdGbJUGO GdLRFj (B: (3fXQI YGeI aj Yde GdGbJUGO , GdWdH h eQhfGJ GdWdH , GdYQV h eQhfGJ GdYQV , fXQjGJ Sdhc GdeSJgdc , fXQjI GdGfJGL h JcGdja GdGfJGL , fXQjI GdShb (B2) (3GdGbJUGO Gdcdj (B: (3GdfGJL Gdbhej h GdONd Gdbhej , GdJVNe h GdHWGdI , GdfbhO h GdbhGYO GdfbOjI , GdLgGR GdeUQaj h GdSjGSI GdfbOjI , GdSjGSI GdeGdjI , GdJVNe GdQchOj , GdJLGQI GdOhdjI h GdJfejI GdGbJUGOjI , eY hLhO CSFdI Mhd GdGbJUGO GdLRFj h GdGbJUGO Gdcdj (B.s
(3eQGLY U(B.501 (3; bGFeI GdeUWdMGJ U(B.509s
Keywords: (3GdGbJUGO GdLRFjs; (3GdGbJUGO Gdcdjs; (3Yde GdGbJUGOs